2009
DOI: 10.1097/wnr.0b013e328330377a
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion and micro-rejection: event-related potential response predicts mitigated distress

Abstract: We studied time-based neural activity with event-related potentials (ERPs) in young adults during a computer-simulated ball-toss game. Experiencing fair play initially, participants were ultimately excluded by other players. Dense-array ERPs showed time-dependent associations between slow-wave activity (580–900 ms) in left prefrontal/medial frontal cortical regions for exclusion events and self-reported distress. More subtle ‘micro-rejections’ during fair play showed a similar distress to ERP association (420–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 19 publications
5
70
1
Order By: Relevance
“…Immediately after the game, children completed the Need Threat Scale, a reliable and valid 21-item ostracism distress measure which has been related to ERPs in this dataset (Crowley et al, 2010) and other studies (Crowley et al, 2009; White et al, 2012). In addition, rejection distress has been linked to fMRI BOLD signals in regions of the medial frontal cortex (Eisenberger et al, 2003; Gunther-Moor et al, 2012; Masten et al, 2009; Rotge et al, 2015).…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…Immediately after the game, children completed the Need Threat Scale, a reliable and valid 21-item ostracism distress measure which has been related to ERPs in this dataset (Crowley et al, 2010) and other studies (Crowley et al, 2009; White et al, 2012). In addition, rejection distress has been linked to fMRI BOLD signals in regions of the medial frontal cortex (Eisenberger et al, 2003; Gunther-Moor et al, 2012; Masten et al, 2009; Rotge et al, 2015).…”
Section: Methodsmentioning
confidence: 90%
“…In humans, the potency of the experience is so strong that it triggers distress even when the excluders are fictitious (Crowley et al, 2009; Zadro et al, 2004) or from despised outgroups (Gonsalkorale and Williams, 2007). In real world situations, social exclusion negatively impacts physical and mental health (Cohen and Janicki-Deverts, 2009; Holt-Lunstad et al, 2010), reflected in lower levels of self-esteem (Deater-Deckard, 2001) and poorer academic self-confidence (Buhs, 2005), as well as higher levels of aggression, depression, and anxiety (Ladd, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These experimental paradigms provide an important first step in understanding the basic neural response to these salient infant stimuli, but more dynamic ERP paradigms will be a valuable addition. For instance, a number of studies in adults and children have examined the neural correlates of social exclusion using a virtual ball-toss paradigm where participants are both included and excluded by fictional players (Crowley et al, 2009; Crowley, Wu, Molfese, & Mayes, 2010; Williams, Cheung, & Choi, 2000; Williams & Jarvis, 2006). Building on this work, one study reported that the level of dismissing attachment in an early adolescent sample was associated with the ERP response to social exclusion by unfamiliar peers (White et al, 2012).…”
Section: Summary and Future Directionsmentioning
confidence: 99%